Feeding site selection by woodland caribou in north-central British Columbia - Johnson, Chris J.; Parker, Katherine L.; Heard, Douglas C. (Rangifer, 2000)
We examined the foraging habits of the northern woodland caribou ecotype {Rangifer tarandus caribou) at the scale of the individual feeding site. Field data were collected in north-central British Columbia over two winters (Dec 1996-Apr 1998). We trailed caribou and measured vegetation characteristics (species composition and percent cover), snow conditions (depth, density, and hardness), and canopy closure at terrestrial and arboreal feeding sites, and at random sites where feeding had not occurred. Logistic regression was used to determine the attributes of feeding sites that were important to predicting fine scale habitat selection in forested and alpine areas. In the forest, caribou selected feeding sites that had a greater percent cover of Cladina mitis and Cladonia spp, lower snow depths, and a lower percentage of debris and moss. Biomass of Bryoria spp. at the 1-2 m stratum above the snow significantly contributed to predicting what trees caribou chose as arboreal feeding sites. In the alpine, caribou selected feeding sites with a greater percent cover of Cladina mitis, Cladina rangiferina, Cetraria cucullata, Cetraria nivalis, Thamnolia spp., and Stereocaulon alpinum as well as lower snow depths.